Success factors in clinical teaching: An integrated pedagogical approach. - Sellberg, Malin; Elmberger, Agnes; Bolander Laksov, Klara; Halvarsson, Alexandra (Physiotherapy Theory & Practice, 2025)
Introduction: Clinical learning has an important role in health care education. However, challenging working environments with increasing staff turnover, sick leave and high work pace create tensions between teaching and clinical activities. After participation in a faculty development program, a teacher team implemented new activities, the supervisors were grouped in pairs for support; a workshop was created for sharing experiences; and a video about feedback was produced. Objectives: To explore and describe supervisors' perceptions of workplace-based interventions to develop quality in supervision in a clinical learning environment, we posed the research question: How did physiotherapy supervisors perceive the interventions during their supervision? Methods: A qualitative study was conducted. Data was collected using focus group interviews with clinical physiotherapist supervisors (n = 12) and analyzed with inductive qualitative content analysis. Results: One overarching latent theme was identified: an integrated and structured pedagogical approach was key to manage clinical learning. Three categories were identified: The teacher team contributed to structure and a sense of coherence, increased opportunity for collegial collaboration, and clarification of tasks and roles decreased experience of stress. Conclusion: The teacher team and the learning activities implemented contributed to an integrated pedagogical approach where collegial collaboration was beneficial for both new and experienced supervisors. Through the testing of new approaches, the clinical supervisors reported that their educational work was made more visible and attractive and that the well-functioning organization made a difference.